3D tomographic reconstruction of irregular rough particles from interferometric images. (September 2022) - Delestre, Barbara; Abad, Alexis; Talbi, Mohamed; Fromager, Michael; Brunel, Marc
Highlights: 3D Tomographic reconstruction of irregular rough particles from their interferometric images. The error-reduction algorithm and the filtered back-projection are used. Centrosymmetric and non-centrosymmetric particles are tested. Abstract: Using a Digital Micromirror Device (DMD), the 3D-reconstruction of programmable rough particles (centrosymmetric or non-centrosymmetric) are done from a set of 120 interferometric images. This can be done using the error-reduction (ER) algorithm for the 2D shape reconstructions and the filtered back-projection for the 3D tomographic reconstruction.